Learning style of accounting students in Universiti Utara Malaysia: An exploratory study - Mat Noh, Masanita; Muhammad, Faidzulaini (Universiti Utara Malaysia, 2004)
Accounting education research during the last two decades has called for continuous efforts to identify and improve the learning styles of undergraduates. Research efforts should continue ti identify for valid instruments to measure students' learning styles, so that accounting educators can reliably use information from these instruments to improve the learning process. This study attempts to probe the learning styles of Universiti Utara Malaysia accounting students. The preferred learning styles of UUM accounting students are identified and recommendations are made to effective learning preferences.